1991
DOI: 10.1381/096089291765561231
|View full text |Cite
|
Sign up to set email alerts
|

Why the Operation I Prefer is Vertical Banded Gastroplasty 5.0

Abstract: Vertical banded gastroplasty (VBG) is easy for the patient, requiring no nasal gastric tube, gastrostomy, feeding enterostomy, or central venous line. Clear liquids are begun the first morning and pursed foods the second day. VBG with a 5.0 cm collar and a 13 ml pouch provides sufficient weight control with minimal risk and side effects. Splenectomy risk is 0.3%, peritonitis from leak 0.6% and operative mortality 0.24%. VBG causes no malabsorption or bacterial overgrowth because there are no blind segments. VB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…Superobese patients are known to have lower EWL than morbidly obese patients [13,14], especially after the lap-Band procedure [25,26]. Although superobese patients need to lose more pounds to achieve the same EWL (because of the larger denominator), these patients also need to lose more weight to have a significant metabolic response in terms of resolution of their comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superobese patients are known to have lower EWL than morbidly obese patients [13,14], especially after the lap-Band procedure [25,26]. Although superobese patients need to lose more pounds to achieve the same EWL (because of the larger denominator), these patients also need to lose more weight to have a significant metabolic response in terms of resolution of their comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of obesity varies with age, sex, ethnicity, race, and socioeconomic status [10]; therefore, the degree of weight loss after bariatric surgery could vary according to some or all of these factors. Different studies have compared weight loss between different ethnic groups [11,12], patientsÕ weight [13,14], type of surgery [15,16], or even different techniques of the same operation [13]. Many of these studies have shown subtle or major differences in outcome, but we are unaware of studies aimed to identify predictors of better weight loss in a large cohort undergoing the same operation (laparoscopic gastric bypass).…”
mentioning
confidence: 99%
“…Vertical Banded Gastroplasty VBG nach Mason [9]: 1 % Gastric Banding in der Technik nach Molina [10]: 1 % rungszufuhr. Um Patienten maximal zu motivieren und Komplikationen wie Mineralstoff-und Vitaminmangel zu vermeiden, sind regelmäûige Nachuntersuchungen unabdingbar.…”
Section: Operationsmethodenunclassified
“…Die chirurgische Therapie der extremen Adipositas hat 2 Therapieansätze, da Liposuktion und Dermolipektomie [6] nur lokale Fettdepots behandeln: · Einschränkung der Nahrungszufuhr durch Eingriffe am Magen (Gastric Bypass, vertikale Gastroplastik, anpaûbares Magenband) [11,12,26] und · Einschränkung der resorbierenden Oberfläche (Jejunoileostomie, biliopancreatic diversion, Duodenumbypass) [9,10,17,31].…”
Section: Diskussionunclassified